55.9k views
2 votes
Use elimination to solve the system of equations.

4y + 3x = -6
y-x=-5
How can you eliminate the z-terms in this system?
4y + 3x = -6
Y-=-5 +
KO
Multiply by ? on both sides.
2
3
4
5
O

2 Answers

1 vote

Answer: 3

Explanation:

User Cancan
by
5.8k points
5 votes

Answer:

(b) 3

Explanation:

You want to know what needs to multiply the second equation in order to solve the system by eliminating the x-variable.

  • 4y +3x = -6
  • y -x = -5

Elimination

The variable x will be eliminated from the system if the equations can be added together with opposite coefficients for x.

The first equation has an x-coefficient of +3, and the second equation has an x-coefficient of -1. These can be made opposite by multiplying the second equation by 3.

To eliminate the x-terms in the system, multiply y-x = -5 on both sides by 3, choice B.

__

Additional comment

The result of adding the equations will then be ...

(4y +3x) +(3y -3x) = (-6) +(-15)

7y = -21

y = -3

x = y +5 = 2

<95141404393>

User Multimedia Mike
by
4.5k points